Design of E-Commerce Learning Media with Blended Learning Method in Vocational Higher Education - Azizah - Azizah; Isnaini - Nurkhayati; Endang - Sulistiyani; Winarto - Winarto (Politeknik Negeri Semarang, 2020)
E-Commerce has experienced very rapid development in Indonesia in recent years. Its practical, making shopping easier and even cheaper, makes people interested in connecting with the world of e-commerce. Given the importance of students' alacrity in dealing with the world of e-commerce, important material related to e-commerce is taught to students. Seeing from these problems, it is appropriate to build a learning media that can help students in their efforts to understand the e-commerce business. The learning media used are based on blended learning, where the learning process is carried out through two main elements, namely classroom learning (classroom lessons ) and learning with online learning. In this study, the first thing to do is to describe in full and detail any material that will be delivered to students in E-Commerce courses, referring to SAP and Silabi. The next step is to make observations in class and distribute questionnaires to students to map in detail which materials are easy, medium and which are difficult. From these results, an E-Commerce course learning flow was made which represents the learning model of blended learning which will then be implemented as a learning media